2019
DOI: 10.1101/2019.12.19.877373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermal cycling protects SH-SY5Y cells against hydrogen peroxide and β-amyloid-induced cell injury through stress response mechanisms involving Akt pathway

Abstract: AbstractNeurodegenerative diseases (NDDs) are becoming a major threat to public health, according to the World Health Organization (WHO). The most common form of NDDs is Alzheimer’s disease (AD), boasting 60-70% share. Excessive aggregation of β-amyloid protein (Aβ) and neurofibrillary tangles has been deemed the major cause for the pathogenesis of AD. A growing number of evidences from studies, however, have suggested that reactive oxygen species (ROS) also play a key role in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 56 publications
3
13
0
Order By: Relevance
“…As shown in Fig 7A , the result shows significant recovery of the Aβ-inhibited viability of SH-SY5Y cells after TC-HT treatment, whose neuroprotective effect could be attributed to activation of Akt and its downstream signalling pathways, as suggested in our previous study [32]. It has been reported that early administration of antioxidants may block the construction of neuroprotection via these pathways [61][62][63], which is in Overall, the study validates the therapeutic potential of TC-HT for AD in vivo, shedding light on development of alternative AD treatment with high efficacy.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…As shown in Fig 7A , the result shows significant recovery of the Aβ-inhibited viability of SH-SY5Y cells after TC-HT treatment, whose neuroprotective effect could be attributed to activation of Akt and its downstream signalling pathways, as suggested in our previous study [32]. It has been reported that early administration of antioxidants may block the construction of neuroprotection via these pathways [61][62][63], which is in Overall, the study validates the therapeutic potential of TC-HT for AD in vivo, shedding light on development of alternative AD treatment with high efficacy.…”
Section: Discussionsupporting
confidence: 73%
“…Development of AD drugs has been confronted with two major obstacles, namely blood-brain barrier (BBB) and severe side effects [14,46]. Hence, the application of heat has potential as an alternative AD treatment, due to its capability to intensify neuroprotective effect [32] and sidestep BBB, targeting the diseased brain directly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alzheimerʼs disease (AD), a neurodegenerative disease closely related to age, is characterized by progressive degeneration and neuronal necrosis, leading to memory loss, cognitive impairment, and behavioral impairment (Chen et al, 2020; Martins et al, 2019). As the global population ages, AD is becoming increasingly common, causing great harm to patients and their families, and becoming a global health concern.…”
Section: Introductionmentioning
confidence: 99%